Manuel Quintín Lame: Legal Thought as Minor Jurisprudence - Julieta Lemaitre (Law Text Culture, 2017)
Manuel Quintín Lame (1880-1967) was an indigenous peasant leader in southern Colombia who wrote profusely about law and justice, mostly petitions to authorities, but also open letters about land rights for his followers and sympathizers. He demanded collective land rights for the remaining indigenous peoples, based on a creative interpretation of existing statutory law, on a strategic use of neo-scholastic jurisprudence and on his own reported visions and hallucinations. Lame’s lawyering de-territorialized legal expertise by claiming to be both indigenous and a lawyer, performing that authority in tandem with appeals to poetry and emotion. In his alternative vision, the social contract is not a pact among equals, but instead a fragile armistice between an invading army and a vanquished people, justified in their disobedience by the very theory he challenges. Can Lame´s writings be read today as jurisprudence, in the intriguing mode of a minor jurisprudence? Perhaps: he is certainly speaking from a minor location, from a situated, historical subordinate position that uses the dominant language of law, its ideas and canon, not to represent or speak-for a group, but instead to destabilize the complacency of the majority, and suggest alternatives.